EBV, CMV, and BK viral infections in pediatric kidney transplantation: Frequency, risk factors, treatment, and outcomes. (24th November 2021) - Levi, Shelly; Davidovits, Miriam; Alfandari, Hadas; Dagan, Amit; Borovitz, Yael; Bilavsky, Efraim; Landau, Daniel; Haskin, Orly
Abstract: Background: Improved short‐ and long‐term outcomes of kidney transplantation have been achieved over the past decades due to improved immunosuppression. This may have increased the risk for infections and, particularly, for the viral infections: cytomegalovirus (CMV), Epstein‐Barr virus (EBV), and polyoma BK virus (BKV). Methods: A retrospective review of viremic CMV, EBV, and BKV infections in pediatric renal transplant recipients treated and followed by a national referral center over a 10‐year period. Results: Sixty‐seven patients (68% males) received 68 kidney grafts (62% from living donors) during the study period; the mean follow‐up period was 5.2 ± 2.4 years. Twenty‐seven viremic episodes were documented (CMV: 13, EBV: 6, BKV: 8) in 24 patients (35.2%). The median time (interquartile range) to viremia post‐transplant was 11 (4–38) months. The viral infection rate was significantly higher in the years 2014–2015 than in previous years (61% vs. 29%, p  = .017). Compared to patients who did not develop viremia, patients with viremias were younger at the time of transplantation, were more likely to receive thymoglobulin induction pre‐transplant and to develop an acute rejection. Multiple logistic regression modeling identified transplant year and recipient's age as significant risk factors for viremia. Graft outcome and eGFR at the last follow‐up was similar between patients who did and did not develop viremia. Conclusions: Viral infections continue to be a major cause of morbidity in pediatric kidney transplant recipients. However, with close monitoring and prompt intervention, patient and renal outcomes remain favorable.